The financial sustainability of state-owned enterprises in an emerging economy - Lee Chee Loong; Riayati Ahmad; Wing Shing Lee; Norlin Khalid; Zulkefly Abdul Karim (Economies, 2022)
When the government creates state-owned enterprises (SOEs), one of the primary purposes is to reduce its financial burden in the long run, also called financial sustainability. Nonetheless, previous research has pointed out that SOEs struggle to achieve financial sustainability due to government intervention. In this study, we examine the relationship between the financial sustainability of SOEs and government intervention in Malaysia. We take a novel approach, using share ownership to measure government intervention. Our results show that the threshold effect of government ownership on financial sustainability in Malaysia is around 27%. The findings prove that the SOEs of an emerging country could reach financial sustainability only if the government ownership is below the threshold. Finally, this study discusses the policy implications of our findings for SOEs. The government of Malaysia should propose a road map to gradually reduce its ownership of SOEs below the threshold.
Keywords: 330; emerging economies; financial sustainability; government ownership; state-owned enterprises; threshold effect